Evidence for genetic hybridization between released and wild game birds: phylogeography and genetic structure of Chukar Partridge, Alectoris chukar, in Turkey - Albayrak, Tamer; García, José Antonio Dávila; Özmen, Özlem; Karadas, Filiz; Ateş, Duygu; Wink, Michael (Diversity, 2022)
The Chukar Partridge (Alectoris chukar, Galliformes) is one of the most important game birds in its native range, spanning from the Balkans to eastern Asia, and the regions of Europe, North America and New Zealand where it was introduced. Previous studies found two main genetic lineages of the species forming an eastern and a western clade. Chukar Partridges are raised in game farms and released to supplement natural populations for shooting in the USA, Canada, Greece, and Turkey. To explore intraspecific genetic structure, phylogeography, and possible genetic admixture events of A. chukar in Turkey, we genotyped individuals from fourteen wild and five captive populations at two mitochondrial and ten microsatellite DNA loci in. Wild and farmed Chukar Partridge samples were analyzed together to investigate possible influences of intraspecific hybridizations. We found that the farmed chukars, which mainly (85%) cluster into the eastern clade, and wild ones were genetically distinct. The latter could be separated into six management units (MUs), with partridges from Gökçeada Island in the Aegean Sea forming the most divergent population. Intraspecific hybridization was detected between wild and captive populations. This phenomenon causes rampant introgression and homogenization. The phylogeographic analysis revealed admixture among wild populations; nevertheless, this did not impair pointing to Anatolia as likely having a “refugia-within-refugia” structure. We recommend that the genetic structure of Chukar Partridge and its MUs be taken into account when developing the policy of hunting, production, and release to preserve the genetic integrity of this species.